Characteristics and Impacts of Water–Thermal Variation on Grain Yield in the Henan Province, China, on Multiple Time Scales - Xuefang Feng; Feng Wu; Songmei Zai; Donglin Wang; Yuzhong Zhang; Qihui Chai (Agronomy, 2023)
Water and thermal resources are changing significantly because of climate change, further affecting important crops, such as grains, worldwide. Previous studies on climate change trends and their impacts on grain yield were mainly conducted on a single time scale, with few studies conducted on multiple time scales. Therefore, here, climate data and grain yield statistics from 1978–2021 in the Henan Province were used to assess how water and thermal changes impact grain yield on multiple time scales. Water and thermal variation were analyzed using the least squares method, Mann-Kendall method, and wavelet analysis method, and grain yield impacts were analyzed using gray correlation method. Results showed increasing trends for ≥0 °C and ≥10 °C accumulated temperature and precipitation, with decreased precipitation in spring. The lowest daily minimum temperature increase was 2–3 times the highest daily maximum temperature. Additionally, grain yield fluctuations were caused by climate change. Climate change affected grain yield on all time scales, fluctuating more in autumn than in summer, which was mainly due to changes in temperature followed by precipitation and extreme precipitation. This study provides a scientific basis for the maintenance of food security under climate change.